Evaluasi Implementasi Kebijakan Dalam Penanggulangan Bencana Banjir Studi Kasus di Kawasan Perumahan Pondok Gede Permai, Jatiasih, Kota Bekasi Periode 2013-2014 - Adinda Nurul Hikmah; Edi Santoso (Journal of Politic and Government Studies, 2017)
ABSTRACTThe purpose of this research to knowing the evaluation of implementationpolicy in flood disaster management adopted by the local government in a residentialarea of Pondok Gede Permai (PGP), Bekasi City, period 2013-2014. Pondok GedePermai (PGP) as the worst locations from the disaster effect with the water depthreached ± 5 meters in 2013 and ± 3.5-4 meters in 2014 caused by high rainfall,damaged embankments, and run-off water. This flood disaster not just happened when adisaster occurs that repeated five years namely in 2002, 2007, and 2013 but it hashappened since 1993, 1997, and 2005. Policy such as embankments repairs has beendoing since Bekasi District authority until their administrative transition into BekasiCity. This raises several issues that can be studied is how the implementation policy wasto do? How is the evaluation from that implementation policy? And, what the factorsencountered in flood disaster management in residential area of PGP?This research uses a mixed methodology approach to evaluation byWilliam Dunn. The population in this research is a residential community in PondokGede Permai, Jatiasih, Kota Bekasi. Sampling technique used is non probabilitysampling with purposive sampling type and the total sample is 95 respondents. Thetechnique of collecting data through observation, structured interviews, questionnaires,and literature study. Data were analyzed using a combination of approaches, namelyquantitative questionnaires with the highest score of 5 (five) and the lowest value of 1(one) as well as qualitative data with reduction, data presentation, and drawconclusions.2The results in this research indicate that the evaluation of theimplementation policy conducted by the local government of Bekasi City consideredsuccessful by the majority of people with an average value of 54% of the totalrespondents. Recommendations for the research is need cooperation between thegovernment of Bekasi City, Bogor District, and the Central Government; embankmentsimprovements made permanent and need for budget transparency and developers; localgovernments more empowering community organizations; extra facilities and budgetfor disaster management; and etc.Keywords: evaluation, implementation, policy, flood, disaster management